DIVERSITY OF DROSOPHILIDAE FROM ČURUG (SERBIA) WITH NOTE ON INVASIVE SPECIES Drosophila suzukii - Sofija Pavkovic-Lucic; Luka Lucic; Jelena Trajkovic; Vukica Vujic; Vladimir Tomic; Tatjana Savic; Vladimir Kekic (Journal of Animal and Plant Sciences, 2026)
Drosophilidae fauna is represented by over 60 species in Serbia and the surrounding countries of the Balkan Peninsula, including the highly invasive Drosophila suzukii. As polyphagous pest that infests a wide range of cultivated fruits, this species has a negative economic impact on both fruit and wine production. This paper presents the results of faunistic investigation of Drosophilidae conducted on Biserno ostrvo, near Čurug (Vojvodina, Serbia) in September 2023. Flies were captured in a semi-domestic habitat, during morning and evening hours, using mixed fruit traps. A total of 17 species was recorded, classified into three genera: Drosophila (14 species), Scaptomyza (2 species) and Chymomyza (1 species). D. suzukii was the most abundant species among fly samples, encompassing over 60% of more than 6000 captured individuals, followed by D. immigrans and D. subobsura. This field research confirmed that Drosophilidae fauna has changed dramatically in the last more than three decades. Namely, the results of the present study were compared with the results of faunistic studies conducted at the same locality in 1989, 2000 and 2002. First of all, invasive D. suzukii displaced previously dominant species, D. melanogaster at this locality. However, in spite of such high abundance of D. suzukii in recent research, the next significant change refers to more diverse Drosophilidae fauna when comparing 2023 study with previous ones, as a result of increased habitat heterogeneity. Based on the results, future research would include the seasonal dynamics of Drosophilidae species, above all D. suzukii, which is important in the context of controlling its abundance.
Keywords: Drosophilidae; Serbia; field study; diversity; Drosophila suzukii